Erstes Kapitel des Buches "Richard und Samuel" : Die erste lange Eisenbahnfahrt (Prag-Zürich) - Brod, Max, 1884-1968; Kafka, Franz, 1883-1924 (Salt Lake City, UT : Project Gutenberg, 2011)
"Erstes Kapitel des Buches 'Richard und Samuel'" by Max Brod and Franz Kafka is a collaborative work written in 1911. Two friends, Richard and Samuel, embark on a train journey from Prague to Zurich, each recording their own perspective in diary form. Their diverging viewpoints reveal tensions beneath the surface of male friendship. When they encounter a spirited young woman named Dora, their contrasting personalities one introspective, one outward-looking become increasingly apparent. The collaboration ended after this single chapter, as both authors found their differences too difficult to reconcile. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Richard_and_Samuel Wikipedia page about this book: https://de.wikipedia.org/wiki/Richard_und_Samuel
Release date is 2011-12-23
Produced by Jana Srna
Keywords: Young men -- Fiction; Male friendship -- Fiction; Voyages and travels -- Fiction; Unfinished books